Association of triglyceride-glucose index with atherosclerotic cardiovascular disease and mortality among familial hypercholesterolemia patients - Wen, Jun; Pan, Qi; Du, Lei-Lei; Song, Jing-Jing; Liu, Yu-Peng; Meng, Xiang-Bin; Zhang, Kuo; Gao, Jun; Shao, Chun-Li; Wang, Wen-Yao; Zhou, Hao; Tang, Yi-Da (Diabetology and metabolic syndrome, 2023)
Familial hypercholesterolemia (FH) is an inherited metabolic disorder with a high level of low-density lipoprotein cholesterol and the worse prognosis. The triglyceride-glucose (TyG) index, an emerging tool to reflect insulin resistance (IR), is positively associated with a higher risk of atherosclerotic cardiovascular disease (ASCVD) in healthy individuals, but the value of TyG index has never been evaluated in FH patients. This study aimed to determine the association between the TyG index and glucose metabolic indicators, insulin resistance (IR) status, the risk of ASCVD and mortality among FH patients. Data from National Health and Nutrition Examination Survey (NHANES) 1999-2018 were utilized. 941 FH individuals with TyG index information were included and categorized into three groups: < 8.5, 8.5-9.0, and > 9.0. Spearman correlation analysis was used to test the association of TyG index and various established glucose metabolism-related indicators. Logistic and Cox regression analysis were used to assess the association of TyG index with ASCVD and mortality. The possible nonlinear relationships between TyG index and the all-cause or cardiovascular death were further evaluated on a continuous scale with restricted cubic spline (RCS) curves. TyG index was positively associated with fasting glucose, HbA1c, fasting insulin and the homeostatic model assessment of insulin resistance (HOMA-IR) index (all p < 0.001). The risk of ASCVD increased by 74% with every 1 unit increase of TyG index (95%CI: 1.15-2.63, p = 0.01). During the median 114-month follow-up, 151 all-cause death and 57 cardiovascular death were recorded. Strong U/J-shaped relations were observed according to the RCS results (p = 0.0083 and 0.0046 for all-cause and cardiovascular death). A higher TyG index was independently associated with both all-cause death and cardiovascular death. Results remained similar among FH patients with IR (HOMA-IR ≥ 2.69). Moreover, addition of TyG index showed helpful discrimination of both survival from all-cause death and cardiovascular death (p < 0.05). TyG index was applicable to reflect glucose metabolism status in FH adults, and a high TyG index was an independent risk factor of both ASCVD and mortality.